Toxicological Evaluation of Progesterone in Nile Tilapia (Oreochromis niloticus) biomarkers Avaliação Toxicológica da Progesterona em biomarcadores de Tilápia do Nilo (Oreochromis niloticus) - Rocha C.S.* (2022)
© 2022, Reativar Ambiental. All rights reserved.The growing use of pharmaceuticals and the scarce legislation on the toxicological effects of these emerging contaminants in aquatic biota, makes studies aimed at their evaluation in the environment of paramount importance.That said, the objective of this job was to evaluate the toxicity of synthetic progesterone, a hormone widely used mainly by women as a contraceptive method, as a toxic agent in relation to biomarkers in fish. Therefore, the experiment consisted primarily of the acclimatization of Oreochromis niloticus specimens popularly known as Nile Tilapia.Subsequently, these specimens were subjected to sublethal concentrations of 200; 400; 600 and 800 μg. L-1 compared to the control group for 96 hours.After exposure, tissues referring to the liver and gills were collected to analyze the enzymatic activities of catalase (CAT) and glutathione-S-transferase (GST) and the brain tissue to evaluate the activity of the acetylcholinesterase (AChE) enzyme.The results obtained in the study showed a total inhibition of AChE enzymatic activity among all exposed samples compared to the control group in the fish brain.Regarding catalase, there was a positive change in both tissues analyzed, with an increase mainly in the concentration of 600 μg. L-1, and as to glutathione-s-transferase, there were no major changes in its activities.This way, it is evident that synthetic progesterone was able to change the mechanism of action of enzymes, especially in the central nervous system of fish, influencing behavioral and physiological changes in the specie tested.